Effects of tracheal intubation without muscle relaxants on postoperative recovery conditions in patients with obstructive sleep apnea: A double-blind randomized controlled study - Soyalp, Celaleddin; Emre Tuncdemir, Yunus; Yuzkat, Nureddin; Gulhas, Nurcin (Annals of Medical Research, 2021)
Aim: We aimed to compare intubation with and without neuromuscular blocking agents with regard to intubation success, hemodynamic parameters, and postoperative recovery in Obstructive sleep apnea patients.Materials and Methods: The study included 60 patients with a STOP-Bang (Snoring, Tiredness during daytime, Observed apnea, high blood Pressure, Body mass index, Age, Neck circumference, Gender) score of ≥3. The patients were randomly divided into two groups: (I) rocuronium group (Group E) and (II) remifentanil group (Group R). Group R received 4 mcg/kg remifentanil and Group E received 0.6 mg/kg rocuronium and then the patients’ intubation difficulty scale scores and their responses to train-of-four (TOF) nerve stimulation, and postoperative recovery were evaluated in both groups.Results: The median time to recovery of the TOF ratio to 0 following anesthetic induction was significantly higher in Group R compared to Group E (p0.001). The overall incidences of postoperative sore throat and hoarseness were remarkably high (p0.002 and p0.001, respectively). The numbers of patients with relaxed vocal cords and complete jaw relaxation were significantly higher in Group E compared to Group R (p0.001). Conclusion: The results indicated that rocuronium provides better intubation conditions and leads to less peri- and post-operative complications compared to remifentanil.Keywords: Obstructive sleep apnea syndrome; intubation without muscle relaxants; postoperative recovery; stop bang tracheal intubation.
Keywords: Obstructive sleep apnea syndrome; intubation without muscle relaxants; postoperative recovery; stop bang tracheal intubation.